Können wir uns entscheiden, etwas zu glauben? Zur Möglichkeit und Unmöglichkeit eines doxastischen Willens - Schmidt, Sebastian (Grazer Philosophische Studien, 2016)
I argue that believing at will – i.e. believing for practical reasons – is in some sense possible and in some sense impossible. It is impossible insofar as we think of belief formation as a result of our exercise of certain capacities (perception, memory, agency). But insofar as we think of belief formation as an action that might lead to such a result (i.e. a deliberation or an inquiry), believing at will is possible. First I present and clarify the problem and its philosophical relevance (section 1). I then argue that a belief formation as an immediate reaction to practical reasons is not necessarily equivalent to believing at will, because the causal mechanism that leads to the formation might be deviant (section 2). Finally, I explain the difference between the two meanings of “belief formation” mentioned above, in order to clarify the possibility and impossibility of believing at will (section 3).
Keywords: doxastic voluntarism – believing at will – belief – action – voluntary control